2005
DOI: 10.1073/pnas.0503017102
|View full text |Cite
|
Sign up to set email alerts
|

ELL-associated factors 1 and 2 are positive regulators of RNA polymerase II elongation factor ELL

Abstract: In human cells, the ELL family of transcription factors includes at least three members, which are all capable of stimulating the overall rate of elongation by RNA polymerase II by suppressing transient pausing by the enzyme at many sites along DNA. In this report, we identify the ELL-associated factors (EAF)1 and EAF2 as strong positive regulators of ELL elongation activity. Our findings provide insights into the structure and function of ELL family transcription factors, and they bring to light direct roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 23 publications
2
83
0
Order By: Relevance
“…It has been reported that eaf1 and eaf2/u19 could serve as regulators of transcriptional elongation by in vitro assays (7). This fact raised a question of whether the down-regulation of noncanonical Wnt ligands wnt11, wnt5, and wnt11r in eafs morphants was due to the disruption of the function of eafs in regulating transcriptional elongation.…”
Section: Volume 284 • Number 24 • June 12 2009mentioning
confidence: 91%
See 1 more Smart Citation
“…It has been reported that eaf1 and eaf2/u19 could serve as regulators of transcriptional elongation by in vitro assays (7). This fact raised a question of whether the down-regulation of noncanonical Wnt ligands wnt11, wnt5, and wnt11r in eafs morphants was due to the disruption of the function of eafs in regulating transcriptional elongation.…”
Section: Volume 284 • Number 24 • June 12 2009mentioning
confidence: 91%
“…ELL binds to RNA polymerase II and acts as a transcriptional elongation factor whose targeted deletion leads to embryonic lethality in mice (5,6). Both EAF1 and EAF2, which share significant sequence homology, stimulate ELL elongation activity (7). Studies by Luo et al (8) argued that EAF proteins are important in MLL-ELL leukemogenesis, whereas our previous studies showed that EAF2/U19 inhibits xenograft prostate tumor growth and undergoes down-regulation in prostate cancer cell lines (9).…”
mentioning
confidence: 97%
“…Alternatively, whole cell lysates were prepared as described in SI Methods, and Flag-Alc1 and associated proteins were immunopurified as described (34), except beads were washed with 0.2 M KCl. For expression in Sf21 insect cells, Flag-Alc1 was cloned into a pBacPAK8 (Clontech) derivative, and purified from lysates of infected cells as described (36).…”
Section: Methodsmentioning
confidence: 99%
“…Eaf2 also appears to be important during embryogenesis, particularly for eye development (Li et al, 2003;Maurus et al, 2005). Both Eaf1 and U19/Eaf2 stimulate ELL elongation activity (Kong et al, 2005). In addition, ELL and Eaf1 colocalize to nuclear suborganelles called Cajal bodies thought to be involved in nucleoli formation, RNA processing and transport of small ribonucleoproteins (Gall, 2003;Cioce and Lamond, 2005).…”
Section: Introductionmentioning
confidence: 99%